Surface modification of hemp fabric with sparked titanium and electrophoretically deposited CNTs for reinforced polyester composites - Somjate Veingnon (2018)
In this work, titanium particles and carbon nanotubes were deposited on hemp fabric using sparking and electrophoretic processes to enhance the strength of the fibers and provide surface modification, which improved the mechanical properties of the fiber polyester composite. The tensile strength and impact strength values for the treated fiber composite showed 50.17% and 24.32% increases compared with those of the natural hemp composites. The increase in the fibers' surface roughness, increased the incorporation of the fibers and the matrix, and the anchor-like of the carbon nanotubes provided increased of the composited strength.